If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 3h Solving -12 = 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. -12 + -3h = 3h + -3h Combine like terms: 3h + -3h = 0 -12 + -3h = 0 Add '12' to each side of the equation. -12 + 12 + -3h = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -3h = 0 + 12 -3h = 0 + 12 Combine like terms: 0 + 12 = 12 -3h = 12 Divide each side by '-3'. h = -4 Simplifying h = -4
| 21p+4p^2=-20 | | 9d+11-15d-1=-42 | | y=-49/0 | | 12/30 | | 67y=2(33y+81) | | 13=h-18 | | B/5-9/5 | | -4x=5-(-15) | | m+8m+4m+6= | | 4w-7w=-9 | | 16x^2-8x+14=0 | | .4/x=2 | | h=-16x^2+6x+33 | | 11x-2=4x+12 | | .0525=0.006x+0.0045 | | -2.3-6z-5.3-3z=-8z+5.7 | | 6(c-6)=5(2+c) | | 860=2(2x-65)+2x | | 3b^3-18b=10b-49 | | -x^2+17x-5=0 | | 0.05d-0.2-17=13 | | 8(t-4)-6(4t+3)=-17(t+5)+7 | | x^3+2x^2=150 | | 6x-6-4x=26+x | | 0.35x-1.2=0.2 | | -2=5(x+9)-8x | | 6t-0=5+8b | | 5(x+0.8)=16 | | -5=16t^2+70t+4 | | 2x^2+(3k-1)x+(3k^2-1)=0 | | -9(w-8)-(4w-1)=-14w | | v-8=16 |